Studies on New Emerging Insect-Pest, Burr – Knot Borer of Apple (Malus domestica Borkh) Under High Density Apple Plantation - Kumari, Neelam; Kumari , Mamta (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Shimla district of Himachal Pradesh is an apple growing regions that always experiences attack of many insect pests which alter the quality and production of apples. The attack of these insect-pests generally recorded maximum in the apples grown under high density plantation in district Shimla. This study mainly reports on the relative abundance of burr knot borers under high density apple growing regions for two consecutive years (2021-2022). This survey was conducted from March to December during 2021-2022. During the study period emergence of burr-knot borers started in March coexisting with the pink bud stage of the apple. The mean per cent density i.e., 60.0% and relative density i.e., 10.5% in burr-knot borers were recorded maximum during the year 2021. Highest diversity was recorded during the period of August i.e., 0.85 and 0.84 during 2021 and 2022, respectively.